2012
DOI: 10.2139/ssrn.2109698
|View full text |Cite
|
Sign up to set email alerts
|

Cheating in the Workplace: An Experimental Study of the Impact of Bonuses and Productivity

Abstract: We use an online real-effort experiment to investigate how bonus-based pay and worker productivity interact with workplace cheating. Firms often use bonus-based compensation plans, such as group bonuses and firm-wide profit sharing, that induce considerable uncertainty in how much workers are paid. Exposing workers to a compensation scheme based on random bonuses makes them cheat more but has no effect on their productivity. We also find that more productive workers behave more dishonestly. These results are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Studies with similar results have been conducted around the world by authors such as McGee et al (2006), Lourenco (2010) and Pascual-Ezama, Prelec and Dunfield (2013). However, other studies such as those by Gill et al (2012), Samnani and Singh (2014) and Aguinis, Joo and Gottfredson (2013) indicated that rewarding employees based on performance leads to decreased motivation and increased fraud, employee bullying and other types of unsavoury behaviour in the workplace. Even though the economic theories of efficient compensation forecast a positive relationship between company performance and executive remuneration, the efforts of researchers to document this relationship have been mostly unsuccessful.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Studies with similar results have been conducted around the world by authors such as McGee et al (2006), Lourenco (2010) and Pascual-Ezama, Prelec and Dunfield (2013). However, other studies such as those by Gill et al (2012), Samnani and Singh (2014) and Aguinis, Joo and Gottfredson (2013) indicated that rewarding employees based on performance leads to decreased motivation and increased fraud, employee bullying and other types of unsavoury behaviour in the workplace. Even though the economic theories of efficient compensation forecast a positive relationship between company performance and executive remuneration, the efforts of researchers to document this relationship have been mostly unsuccessful.…”
Section: Introductionmentioning
confidence: 53%
“…Reward systems should not only motivate employees, but also enhance the overall corporate values of the company (Kuo et al 2013). Gill et al (2012) and Shin (2013) suggest that companies with bonus-based pay structures should consider that worker dishonesty might be an unintended consequence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most evidence comes from lab experiments as the identification of relative comparisons in the field is a daunting task. These laboratory studies document, for example, that subjects at the lower end of the income distribution take unwise risk (Kuziemko et al, 2014), that subjects cheat more when they are aware that others earn more (Gill, Prowse and Vlassopoulos, 2013;John, Loewenstein and Rick, 2014) and that subjects with higher earnings do not give more to a charitable cause than subjects with lower earnings (Tonin and Vlassopoulos, 2013). 6 In all these studies the distribution of income is randomly assigned and there is no variation in inequality.…”
Section: Introductionmentioning
confidence: 99%
“…Retailers are also significantly affected by unethical behaviour in workplace. Previous studies have confirmed theft among the key losses for retail business (John et al, 2014;Moorthy et al, 2015) and low-level employees in low-wage sector being a higher risk group for unethical action (Detert et al, 2007;Whysall, 2008;Gill et al, 2013).…”
Section: Introductionmentioning
confidence: 90%